Association of NADPH-Oxidase 2 (NOX2) with the Development of Atopic Asthma - Ibragimov, B.R.; Demertsidis, A.S.; Reshetnikova, I.D.; Skibo, Yu.V.; Abramov, S.N.; Abramova, Z.I. (Biomedical Chemistry: Research and Methods, 2025)
Phagocytic cells destroy bacteria, allergens, and apoptotic cells via antimicrobial reactions coupled with phagocytosis, including generation of reactive oxygen species (ROS) and delivery of hydrolytic enzymes from lysosomes to the phagosome. ROS produced by NADPH oxidase 2 (NOX2), are involved in the mechanism of LC3-associated phagocytosis; they participate in the development of innate and adaptive immune responses, leading to airway remodeling and hyperreactivity. The aim of this study was to investigate an association between NOX2 and the severity of atopic bronchial asthma (ABA). The level of ROS was determined in monocytes of healthy donors and patients with atopic bronchial asthma using dihydrorhodamine 123 (DHR-123). The expression level of NOX2 gene in monocytes of healthy donors and patients with atopic bronchial asthma was analyzed by RT-PCR. In the presence of PMA (phorbol 12-myristate 13-acetate), there was a significant increase in rhodamine-123 (Rho-123) fluorescence in all studied groups. At the same time, a significant increase in the median of Rho-123 fluorescence was found in the group with severe ABA as compared to healthy donors and patients with mild AAA, as well as to the group of patients with moderate ABA. A significant increase in NOX2 gene expression was found in the groups with moderate and severe ABA compared to the other studied groups. Based on the data obtained, it can be assumed that with an increase in the activity of NOX2, the key enzyme of LC3-associated phagocytosis, there is an aggravation of the course of ABA.